2018
DOI: 10.5540/tema.2018.019.02.289
|View full text |Cite
|
Sign up to set email alerts
|

Modelo Entomológico Determinístico sob Efeito da Pluviosidade para o Aedes aegypti e o Aedes albopictus

Abstract: Recebido em 24 de outubro de 2017 / Aceito em 2 de março de 2018 RESUMO. As espécies de mosquitos Aedes aegypti e Aedes albopictus destacam-se na dispersão de diversas arboviroses, dentre elas: a dengue, a febre amarela, a febre chikungunya e o zika vírus. Trabalhos naárea de Biologia Matemática vêm sendo realizados recentemente no intuito de descrever a dinâmica da população destes vetores e, consequentemente, auxiliar os gestores públicos no controle destas arboviroses. Neste trabalho, apresentamos um modelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
7
1
1
Order By: Relevance
“…The number of eggs per positive paddle was similar between both seasons studied, and no influence of accumulated rainfall on the number of eggs on positive paddles was observed. The data provided do not corroborate those reported in literature, where the oviposition process has been usually shown to be dependent directly on breeding site availability (Stein et al 2005, Silva et al 2018). During the dry season, there tends to be a scarcity of larval habitats with decreased rain, leading females to perform complete oviposition in one single container or just a few, which explains the fact that the number of eggs per paddle is usually higher during this period.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The number of eggs per positive paddle was similar between both seasons studied, and no influence of accumulated rainfall on the number of eggs on positive paddles was observed. The data provided do not corroborate those reported in literature, where the oviposition process has been usually shown to be dependent directly on breeding site availability (Stein et al 2005, Silva et al 2018). During the dry season, there tends to be a scarcity of larval habitats with decreased rain, leading females to perform complete oviposition in one single container or just a few, which explains the fact that the number of eggs per paddle is usually higher during this period.…”
Section: Discussioncontrasting
confidence: 99%
“…albopictus populations) observed in the BMA has been demonstrated in other studies. Silva et al (2018), using an entomological model, showed a higher proportion of positive traps related to greater precipitation. However, a negative influence of rainfall on the frequency of positive larval sites has also been shown, with the loss of immature individuals during heavy rains due to a larval site overflow (Urbinatti et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cases of rates of development, outside the roots of the polynomials, the values in the model are fixed to zero, although it never happens in the present range of data. The system (3.1) is non-autonomous because it has coefficients dependent on rainfall and temperature which, in turn, depend o time [20]. However the temperature and precipitation data is updated only weekly and the time evolution is hourly.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Among the arboviruses that are difficult to control is dengue, one of the main public health problems in the world, being transmitted by Aedes aegypti. Accelerated growth was also reported in cases of other diseases from Aedes aegypti, such as Zika and Chikungunya (Silva et al, 2018). It is noteworthy that even with technological advances in the search for vaccines for these diseases, only for yellow fever there is a long-term vaccine, approximately 10 years (Rothman, 2004).…”
Section: Introductionmentioning
confidence: 96%